How Engagement with Gamified Applications Impacts Quality of Life: A Conceptual Model - Abbasi, A.Z. (Springer Science and Business Media Deutschland GmbH, 2021)
This study proposes a conceptual model that establishes a relationship between engagement with gamified applications, and its impact on a userâs quality of life (QoL). Since gamification is rapidly gaining popularity therefore the use of such applications has become a norm. Subjective quality of life is a mental state or an individualâs awareness of factors that impact major aspects of life, such as health, learning, creativity, socialization etc. Literature is sparse when it comes to investigating the impact of engagement with gamified applications, and its effect on quality of life. To address this research gap, we explore how consumer engagement with gamification cultivates an individualâs perception with regards to their quality of life. We posit that consumer engagement is a higher-order formative construct, comprising cognitive, affective and behavioural dimensions, is influenced by gamified applications, leading towards an increase in subjective QoL. QoL is also a higher-order formative construct involving first-order reflective constructs such as leisure time, view of life, creativity, learning, friendship and individualistic perspective of satisfaction. This study provides an important insight to avenues of academia and practitioners by developing a conceptual model where consumer engagement in serious games acts as a predictor of usersâ QoL. We conclude by discussing important implications that arise from this exploration, along with its limitations and avenues for further research. Â© 2021, Springer Nature Switzerland AG.